Reduced Sensitivity in Monilinia fructicola to Propiconazole in Georgia and Implications for Disease Management - Schnabel, Guido (Plant disease, 2004)
Single-spore isolates of Monilinia fructicola were collected from commercial orchards in South Carolina and Georgia with prolonged past exposure to demethylation inhibitor (DMI) fungicides and from an orchard with no DMI history (baseline population). Sensitivity to propiconazole was determined using the concentration in agar media required to suppress radial growth of mycelium by 50% (EC50. Mean EC50 values from six South Carolina populations were not different from the baseline population (P < 0.05). Two of five populations from Georgia revealed (significantly higher mean EC50 values compared with the baseline population (P < 0.05). Isolates with high (AP5 and AP6) and low (DL71 and DL72) EC50 values were selected to determine disease incidence on peach fruit after protective or curative applications of propiconazole at 0.15 or 0.3 liter/ha (half and full label rate, respectively). Disease incidence was significantly greater on peaches inoculated with AP5 and AP6 after curative treatment with propiconazole at 0.15 liter/ha (P < 0.05). Following protective or curative treatments at 0.3 liter/ha, disease incidence was significantly greater for AP6 but not for AP5. These results suggest that a shift toward reduced sensitivity has developed in some M. fructicola populations from Georgia, and that isolates with reduced sensitivity to propiconazole are more difficult to control in the field. Field testing of DMI fungicides, captan, QoI fungicides, and fenhexamid in experimental orchards) indicated that the DMI fungicides are still among the most efficacious products for brown rot (control, and that new products containing QoI fungicides may be viable disease control alternatives or rotation partners